(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, although the written sources that have come down to us do not clearly describe the lives and activities of upper-class women in all their details, the information gleaned from them allows us to shed light on the fate of upper-class ladies, full of joy and anxiety, luxury and humiliation, prestige and oppression, reflecting all the specific aspects and contradictions of their families and times.